Tax Competence of the Eurasian Economic Union: A New Reading by the Court (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
In October 2022, the Court of the Eurasian Economic Union (EAEU) adopted the first Advisory Opinion fully devoted to the interpretation of the tax provisions of the EAEU Treaty. While reiterating its previous findings that the powers to impose taxes fall within the jurisdiction of the Member States, for the first time, the Court has argued in favour of limiting these powers by the law of the EAEU. Such limitations derive from the principles of non-discrimination and free competition of goods and services regardless of the country of production. In such a manner, the Court has made a significant contribution to the establishment of a single common market within the Union and has enriched the understanding of the principles governing the division of competence between the Member States and the bodies of the Union. The only conclusion that could be seen as dubious by the Court was regarding the collection of VAT on the basis of the country of destination and the fact that this is necessary to maintain competition and avoid double taxation and that the reasoning for such a mechanism is also predetermined by the nature of this tax
Keywords: Eurasian Economic Union; Advisory opinion; Indirect taxes; discrimination; Single market; Fair competition